Outcome of Perineal Anastomotic Urethroplasty in the Management of Pelvic Fracture Urethral Injury (Bangladesh Journal of Urology, 2020)
Purpose: This study aims at finding the outcome and complications of perineal end toend posterior anastomotic urethroplasty in the management of posterior urethral injuryresulting from pelvic fracture.Methods: We performed 49 perinealbulbo-prostatic anastomotic urethroplasty for PFUIsfrom January, 2013 to April, 2017. Mean age was 37 years with majority between 21 to50 years (>85%). All were male patients. Three patients had history of failed anastomoticurethroplasty. Patients were selected as per selection criteria; detailed history and preoperativeinvestigations were done and were prepared for operation after adequatecounseling. After surgical intervention patients were discharged with a supra-pubiccatheter (SPC) and per urethral catheter in situ. On 22nd POD urethral catheter wasremoved and SPC on the next day if patient can void normally. 1st and 2nd follow updone on of 3rd and 6th month respectively following surgery. If patient voided well andQmax>15ml/ sec; repair was defined as successful.Results: Success rate of perinealbulbo-prostatic anastomotic urethroplasty for pelvicfracture urethral injury was 89.79%. Total 5 procedures were failed including 1 urethrocutaneousfistula and needed re-do anastomosis. Erectile dysfunction (ED) was presentin 6 patients before operation and after surgery 4 more patients developed ED and totalnumber was 10 during first follow up, which reduced to 8 during second follow-up. Onepatient developed incontinence which improved in subsequent follow-up.Conclusions: Anastomotic urethroplasty remains the cornerstone in the managementof PFUI. A long term follow-up for at least 5 to 10 years is needed to make a comment onultimate outcome of this procedure which may have positive impact in future patientmanagement.Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.75-79